Pengaruh Dept to Equity Ratio (DER) dan Book Value per Share (BVS) terhadap Return Saham pada PT. Bisi Internasional, Tbk. - Ita Purnama; Suryadin Suryadin (Target : Jurnal Manajemen Bisnis, 2022)
This study aims to determine the effect of dept to equity ratio (DER) and book value per share (BVS) on stock return at PT. Bisi International, Tbk. The population in this study is financial statements that have been registered on the IDX from 2007 – 2020, namely 13 years, while the sample used is 10 years, namely from 2011 – 2020 where the sample determination uses purposive sampling, namely using certain criteria, one of which is the completeness of the report. finance. Data collection techniques use documentation and literature study while data analysis techniques use classic assumption tests, multiple linear regression tests, correlation and determination coefficients, t tests and F tests. the effect of book value per share and is significant on stock return, while simultaneously there is the influence of dept to equity and book value per share on stock return at PT. Bisi Internasional, Tbk.